Polymorphisms in TREX1 and susceptibility to HIV‐1 infection. (15th June 2013) - Pontillo, A.; Girardelli, M.; Catamo, E.; Duarte, A. J.; Crovella, S.
Summary TREX‐1 is a restriction factor against HIV‐1. The coding sequence of TREX1 gene was analysed in HIV+ subjects searching for genetic variations possibly associated with the susceptibility to HIV infection. The single nucleotide polymorphism rs3135945 was significantly associated with HIV infection, emphasizing the involvement of TREX‐1 in the anti‐HIV response.